Molecular Design of Amphiphilic Plasma Membrane-Targeted Azobenzenes for Nongenetic Optical Stimulation - Vurro, Vito; Bondelli, Gaia; Sesti, Valentina; Lodola, Francesco; Paternò, Giuseppe Maria; Lanzani, Guglielmo; Bertarelli, Chiara (Frontiers in Materials, 2021)
We present a series of cationic membrane-targeted azobenzene molecules, with the aim to understand how variations in molecular architecture influence the relative optical and biological properties. 1,4-Amino-substituted azobenzene was chosen as the switching unit while the number of linked alkyl chains and their cationic end-group were systematically varied. Their photophysics, membrane partitioning, and electrophysiological efficacy were studied. We found that the polar end group is a key-factor determining the interaction with the phospholipid heads in the plasma membrane bilayer and consequently the ability to dimerize. The monosubstituted photoswitch with a pyridinium-terminated alkyl chain was found to be the best candidate for photostimulation. This study provides a structure-property investigation that can guide the chemical engineering of a new generation of molecular photo-actuators.